2013
DOI: 10.1021/jf403098y
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntioxidant and Antiproliferative Activities of 5-Hydroxymethylfurfural

Abstract: 5-HMF is widely presented in foods and produced through the degradation of hexoses and Maillard reaction during heat treatment of foods containing reducing sugars and amino acids in an acid environment. However, controversial conclusions on the biological effects of 5-HMF have been drawn in previous studies. Therefore, the main aim of this study was to investigate the antioxidant and antiproliferative activities of 5-HMF. The 2,2'-azinobis-3-ethylbenzothiazolin-6-sulfonic acid (ABTS) assay, the 1,1-diphenyl-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
149
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(156 citation statements)
references
References 33 publications
3
149
0
4
Order By: Relevance
“…Most probably, the inhibitory activities of honey polar fractions could be due to the presence of hydroxymethylfurfural. This is because hydroxymethylfurfural has been proven to have high antioxidant capacity as reported by Zhao et al (2013). This study also reported hydroxymethylfurfural could be developed as a novel natural antioxidant with potential application in cancer chemoprevention.…”
supporting
confidence: 59%
“…Most probably, the inhibitory activities of honey polar fractions could be due to the presence of hydroxymethylfurfural. This is because hydroxymethylfurfural has been proven to have high antioxidant capacity as reported by Zhao et al (2013). This study also reported hydroxymethylfurfural could be developed as a novel natural antioxidant with potential application in cancer chemoprevention.…”
supporting
confidence: 59%
“…Based on our HPLC results, four phenolic compounds, 5‐hydroxymethylfurfural (5‐HMF) (0.65 µg/mg), neochlorogenic acid (3.02 µg/mg), protocatechuic acid (0.06 µg/mg), and syringic acid (0.07 µg/mg) were identified in pectinase‐treated P. mume concentrate. Many studies have proposed that treatment with 5‐HMF (Zhao et al., ), neochlorogenic acid (Fang et al., ; Lin, Hu, Zhou, & Cheung, ), protocatechuic acid (Xie, Guo, Wang, Lei, & Yu, ), and syringic acid (Gheena & Ezhilarasan, ; Hu, Lin, Huang, & Cheung, ) exerts cancer and angiogenesis suppressive activities with regard to several tumor species. Specifically, previous studies reported that 5‐HMF (Zhao et al., ), neochlorogenic acid (Fang et al., ), protocatechuic acid (Xie et al., ), and syringic acid (Gheena & Ezhilarasan, ) inhibited proliferation of various cancer cells at the concentrations of 0.77, 1.77, 25.2, and 4.95 µg/mg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the contribution of this reaction to the increase in the antioxidant activity should not be ruled out. Zhao et al (2013) found that HMF exhibited antioxidant activity by scavenging the DPPH free radicals in a dose-dependent manner. Fares and Menga (2012) observed an increase in the antioxidant activity in toasted chickpea flour and they ascribed this result not only to the total polyphenol content but also to Amadori and Heyn's products between reducing sugars and proteins.…”
Section: Antioxidant Activitymentioning
confidence: 96%